Valuing Environmental Factors in Cost-Benefit Analysis Using Data Envelopment Analysis - Timo Kuosmanen (Fondazione Eni Enrico Mattei (FEEM), 2006)
Environmental cost-benefit analysis (ECBA) refers to social evaluation of investment projects and policies that involve significant environmental impacts. Valuation of the environmental impacts in monetary terms forms one of the critical steps in ECBA. We propose a new approach for environmental valuation within ECBA framework that is based on data envelopment analysis (DEA) and does not demand any price estimation for environmental impacts using traditional revealed or stated preference methods. We show that DEA can be modified to the context of CBA by using absolute shadow prices instead of traditionally used relative prices. We also discuss how the approach can be used for sensitive analysis which is an important part of ECBA. We illustrate the application of the DEA approach to ECBA by means of a hypothetical numerical example where a household considers investment to a new sport utility vehicle.
Keywords: C61; D61; Q51; 330; Cost-Benefit Analysis; Data Envelopment Analysis; Eco-Efficiency; Environmental Valuation; Environmental Performance; Performance Measurement; Umweltbelastung; Kosten-Nutzen-Analyse; Data-Envelopment-Analyse; Theorie; Performance-Messung